Theoretical models for performance analysis of spintronic THz emitters - Yang, Yingshu (2024)
The terahertz (THz) region of the electromagnetic spectrum, spanning from 0.1 to 10 THz, offers unique opportunities for imaging, spectroscopy, and communication applications. However, the potential of THz technologies has been limited by the availability of efficient and versatile THz emitters. Spintronic THz emitters (STEs), leveraging the ultrafast dynamics of electron spins in magnetic materials, have emerged as a promising solution to this challenge. STEs offer significant advantages, including broad bandwidth, high power output, and room-temperature operation, positioning them at the forefront of THz technology development. Despite these advances, understanding the operational principles and improving the performance of STEs remain areas of active research. This review focuses on the theoretical models that describe the behavior of STEs, aiming to provide a comprehensive overview of the underlying physics and suggest directions for future enhancements. Through a detailed examination of these models, the review seeks to clarify the basics of the physics driving STE performance and highlight innovative strategies for their optimization and application expansion.